Formulation and storage effects on pomegranate smoothie phenolic composition, antioxidant capacity and color. (October 2018) - Cano-Lamadrid, M.; Hernández, F.; Nowicka, P.; Carbonell-Barrachina, A.A.; Wojdyło, A.
Abstract: Smoothies are an increasingly popular way of consuming fruits and the industry is focusing on the increment of shelf life and the maintenance original color and the content of bioactive compounds. The aim of the present study was to evaluate how formulation and storage conditions (6 months at 4 or 20 °C) of different pomegranate smoothies affected on functional compounds. Phenolic compounds, antioxidant capacity (ABTS, FRAP) and color of 12 different smoothies were studied. The study was completed evaluating the effect of ratio purée:juice (60:40 or 40:60), pomegranate cultivar ( Mollar de Elche or Wonderful ) and fruit purée (quince, jujube, or fig) on studied smoothies. The smoothies before storage presented high values of total polyphenolic content (TPC): 247–314 mg/100 g fresh weight (fw), 2939–3920 mg/100 g fw, and 3809–5324 mg/100 g fw, in fig, jujube and quinces pomegranate smoothies, respectively. A positive effect of the 40:60 ratio purée:juice, the Wonderful pomegranate juice storing at 4 °C was found on total polyphenolic content [sum of anthocyanins, flavanols, flavan-3-ols (as monomeric and dimeric), polymeric procyanidins and phenolic acids] and quality of smoothies ( a * coordinate) being only a reduction of 30.1%, 13.1% and 9.5% in fig, jujube and quinces smoothies, respectively. Highlights: Red color of pomegranate smoothies was enhanced with quince even after storage. Fig-pomegranate smoothies had higher anthocyanin content before and after storage. Polyphenolic content greatly decreased in fig pomegranate smoothies after storage. Purée:juice 40:60 using Wonderful juice at 4 °C was the best variable combination.